Benchmarking and Objective Selection of Technologies for Housing in India Using Quality Function Deployment - Paul , Virendra Kumar; Seth, Varun (Penerbit Universiti Sains Malaysia, 2017)
The paper identifes technology as a key solution for the challenges of sustainability and quality in housing and recognizes benchmarking as a tool for selection of appropriate technologies. Suitability of technologies for housing has been explored in respect of functional needs, sustainability needs, and performance standards. These issues have brought out the need for an objective methodology for selection of appropriate technologies, especially for mass housing. The objective framework has been developed by identifcation of needs of large scale projects, assessment of current issues and their shortcomings and development of objective parameters. Quality Function Deployment (QFD) has been used as tool for benchmarking. The case example of the technologies promoted by Government of India for “Housing for All” Mission has been taken up for development of the framework and benchmarking. Findings from the QFD process highlight that these emerging technologies cater to limited building elements and not for the building system as a whole. Inconsistencies amongst performance of these technologies on various parameters have been demonstrated. It is concluded that assessment and benchmarking of technologies give useful insights into the comparative performance of each of these technologies and is hence, a useful tool for selection of appropriate technology for housing.